Leech Lake Ojibwa residence - Bromley, Edward A. (Edward Augustus), 1848-1925 photographer. (William L. Clements Library, 1895)
Group portrait of unidentified family of Ojibwa Indians (one man, two children and five women) wearing western clothing posing outside of wigwam.; Contemporary inscription on front: Be it ever so humble, there is no place like home.; Contemporary inscribed image caption on verso: Cross Lake Area Chippewa Lodge 1895.; Title devised by cataloger (contemporary inscribed image caption on verso erroneous).; "Ojibwa Indians" variant names: Anishinaabe, Chippewa Indians, Ojibwe Indians.